Serendipitous Discovery of a Cascade Approach to Perhydrodibenzofuranones Related to the Natural Product Incarviditone - Christou, Stephania; Edwards, Alyn C.; Pritchard, Robin G.; Quayle, Peter; Stratford, Ian J.; Whitehead, Roger C. (Synlett, 2014)
The unexpected discovery of an eliminative deprotection and cyclodimerization cascade reaction sequence led to the preparation of a series of perhydrodibenzofuranones that bear a structural resemblance to the natural product incarviditone. One of the novel dimers was found to show significant antiproliferative activity towards a non-small-cell lung cancer cell line, and represents a useful lead compound for the discovery of more potent anti-cancer agents.
Keywords: natural products; medicinal chemistry; cascade reactions; heterocycles; biomimetics